Common Fixed Point Theorems of Integral Type Contraction on Cone Metric Spaces and Applications - Kumar, Sanjay; Singhal, Akash; Sharma, Manish (Communications in Mathematics and Applications, 2023)
In this paper, we establish the existence and uniqueness of a common fixed point for two pairs of weakly compatible mappings satisfying integral type contractive condition and property (EA) on cone metric spaces, and we prove the existence and uniqueness of a solution for an ordinary differential equation with periodic boundary conditions. The derived results generalized some well-known results that exist in the literature